Characterization of a biodegradable coralline hydroxyapatite/calcium carbonate composite and its clinical implementation. - Fu, K; Xu, Q; Czernuszka, J; Triffitt, J; Xia, Z (Institute of Physics Publishing, 2013)
A partially converted, biodegradable coralline hydroxyapatite/calcium carbonate (CHACC) composite comprising a coral calcium carbonate scaffold enveloped by a thin layer of hydroxyapatite was used in the present study. The CHACC was characterized using powder x-ray diffraction, scanning electron microscopy and energy dispersive x-ray spectroscopy. The ability of the CHACC to promote conductive osteogenesis was assessed in vitro using human mesenchymal stem cells (hMSCs) and in vivo using an immunodeficient mouse model. The clinical performance of CHACC as a bone substitute to fill voids caused by excision of bone tumours was also observed in 16 patients. The CHACC was found to consist of two overlapping layers both morphologically and chemically. Hydroxyapatite formed a thin layer of nanocrystals on the surface and a thick rough crystal layer of around 30 µm in thickness enveloping the rock-like core calcium carbonate exoskeletal architecture. hMSCs cultured on CHACC in osteogenic medium demonstrated significant osteogenic differentiation. After subcutaneous implantation of CHACC incorporating osteogenically differentiated hMSCs and an anti-resorptive agent, risedronate, into an immunodeficient mouse model, bone formation was observed on the surface of the implants. Clinical application of CHACC alone in 16 patients for bone augmentation after tumour removal showed that after implantation, visible callus formation was observed at one month and clinical bone healing achieved at four months. The majority of the implanted CHACC was degraded in 18-24 months. In conclusion, CHACC appears to be an excellent biodegradable bone graft material. It biointegrates with the host, is osteoconductive, biodegradable and can be an attractive alternative to autogenous grafts.